Application of Gamification Models with Virtual Reality for Learning Plant Cultivation Techniques - Suhendi; Norhanifah Murli, (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The aim of this research is to assess the effectiveness of implementing gamification models with virtual reality (VR) for plant cultivation techniques in constructing hydroponic circuits. The purpose of this study is to examine the significant differences in effectiveness between the control group and the intervention group when using gamification with virtual reality. The data used consists of test results from 50 respondents, divided into two groups: a control group of 25 students and an intervention group of 25 students. The trial was divided into two different groups. Group 1, the control group, received conventional treatment, which involved lecturers explaining the assembly of hydroponic circuits in class, followed by students practicing the assembly. Group 2, the intervention group, received self-learning treatment that involved the practice of assembling hydroponic circuits using a gamification model with VR. An independent t-test was conducted to determine whether there was a significant effect of applying plant cultivation techniques on assembling hydroponic circuits. The results of the t-test revealed a significant effect of applying the gamification model with VR compared to the conventional model. The application of the gamification model with VR to assemble hydroponic circuits has shown significant effectiveness, with an N-Gain value of 62.47%, whereas the conventional treatment has demonstrated lower effectiveness, with an N-Gain value of 28.24%.